2019
DOI: 10.1039/c8cp07585a
|View full text |Cite
|
Sign up to set email alerts
|

Ice crystallization observed in highly supercooled confined water

Abstract: We investigate the state of water confined in the cylindrical pores of MCM-41 type mesoporous silica, with pore diameters of 2.8 nm and 4.5 nm, over the temperature range 160–290 K by combining small angle neutron scattering and wide angle diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…The obtained results are in agreement with other studies reported in the literature for supercooled confined water (Soper, 2008(Soper, , 2012(Soper, , 2013. Stefanutti et al (2019) studied the state of supercooled water confined in MCM-41 using neutron scattering. They have shown the coexistence of freezable pore water with a layer of non-freezable pore water by analysing the change in the Bragg peak intensities.…”
Section: Total X-ray Scatteringsupporting
confidence: 91%
“…The obtained results are in agreement with other studies reported in the literature for supercooled confined water (Soper, 2008(Soper, , 2012(Soper, , 2013. Stefanutti et al (2019) studied the state of supercooled water confined in MCM-41 using neutron scattering. They have shown the coexistence of freezable pore water with a layer of non-freezable pore water by analysing the change in the Bragg peak intensities.…”
Section: Total X-ray Scatteringsupporting
confidence: 91%
“…This confinement effect is due to the decrease of the probability of molecules near the wall to escape the cage created by the molecules surrounding them, as part of their cage is created by the pore wall and thus never opens. Notice that, this well established confinement effect [34][35][36][37][38][39][40][41][42][43], displays a number of similarities with the effect of a decrease in temperature in supercooled liquids. As expected, when the motor activates the medium in Figures 4b to 4d, the diffusion inside the pores increases.…”
Section: Resultsmentioning
confidence: 99%
“…Confinement of the liquid inside nano-pores has been seen as a way to cutoff the correlation lengths and obtain indirect informations on them by studying the associated dynamical modifications in the liquid. For that fondamental reason as well as multiple practical applications, confinement has been the subject of a number of studies and is still a subject of active research [3,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Indeed, in supercooled liquids, confinement induces various effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, these ice Bragg peaks appear when h is above 0.4. We note that these Bragg peaks are rather narrow, which indicate that they result from bulk crystals instead of nanometer sized crystals, as the latter will significantly broaden the peaks as seen in [71][72][73][74] . This is further supported by DSC measurement, where no first-order transition is observed at h = 0.3, but it appears at higher hydration levels, h = 0.4 or above.…”
Section: Experimental Evidencementioning
confidence: 87%